Distribution and Clinical Significance of Lupus Anticoagulant and Anticardiolipin Antibody with Systemic Lupus Erythematosus (Journal of Chittagong Medical College Teachers' Association, 2010)
Key words: Systemic lupus erythematosus; lupus anticoagulant; anticardiolipin antibody; thrombosis; neuropsychiatric manifestations; pregnancy loss; thrombocytopenia DOI: 10.3329/jcmcta.v20i1.4929 Journal of Chittagong Medical College Teachers' Association 2009: 20(1):16-22